GENDER DIFFERENCES IN ENGLISH LEARNING STYLE PREFERENCES AMONG SENIOR HIGH SCHOOL STUDENTS - Lia Aprilia (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
When This research objectives were to identify the difference between male and female students in their English learning style, and to identify the most preferred learning styles used by both male and female students in learning English. In achieving the research objectives, the researcher used a descriptive qualitative research design. This research was conducted in one senior high school in Garut, West Java, Indonesia. The researcher used a questionnaire and an interview to collect the research data. There were 29 students involved in this research. The researcher gave the questionnaire to all the participants of this research, and the researcher involved 2 male and 2 female students in the interview session to strengthen the questionnaire result. Based on the results of this research, the researcher concluded some points. Firstly, there was the difference between male and female students in their English learning styles. Secondly, the most preferred learning style used by male students in learning English were kinesthetic learning style (27.59%). Thirdly, the most preferred learning style used by female students in learning English were auditory learning style (34.48%).